Line shape and composition of the In 3d5/2 core-level photoemission for the interface analysis of In-containing III-V semiconductors - J. Mäkelä; M. Tuominen; M. Kuzmin; M. Yasir; J. Lång; M.P.J Punkkinen; P. Laukkanen; K. Kokko; K. Schulte; J. Osiecki; R.M. Wallace (Elsevier, 2022)
The In 3d5/2 photoelectron spectroscopy peak has been widely used to determine the interface structures of In-containing III-V device materials (e.g., oxidation states). However, an unclear parameter affecting the determination of the energy shifts and number of the core-level components, and therefore, the interpreted interface structure and composition, is still the intrinsic In 3d5/2 peak line shape. It is undecided whether the line shape is naturally symmetric or asymmetric for pure In-containing III-V compounds. By using high-resolution photoelectron spectroscopy, we show that the In 3d5/2 asymmetry arising from the emission at high binding-energy tail is not an intrinsic property of InAs, InP, InSb and InGaAs. Furthermore, it is shown that asymmetry of In 3d5/2 peaks of pure III-V’s originates from the natural surface reconstructions which cause the coexistence of slightly shifted In 3d5/2  components with the symmetric peak shape and dominant Lorentzian broadening.